2008
DOI: 10.1111/j.1399-5618.2007.00503.x
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear broad band dynamics are less complex in major depression

Abstract: The evidence for decreased complexity of cardiac regulation in depressed patients presented here might be useful as an indicator of the increased cardiac mortality known in depression, especially since these parameters are capable of predicting cardiac mortality in other diseases. The importance of these parameters for patients at risk should be evaluated in future prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 56 publications
(68 reference statements)
2
32
1
Order By: Relevance
“…First, stress is usually associated with sympathetic, and not parasympathetic predominance [35]. Second, in depression, anxiety and phobia, decreased vagal modulation of heart rate variability has repeatedly been shown [15,16,34,36], and approximately one third of the study population indicated some psychiatric complaints as defined by scores above 60 in the respective categories. Yet, the average of these scores does not indicate overt psychiatric symptoms in the patient population included in this study (see Table 2).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…First, stress is usually associated with sympathetic, and not parasympathetic predominance [35]. Second, in depression, anxiety and phobia, decreased vagal modulation of heart rate variability has repeatedly been shown [15,16,34,36], and approximately one third of the study population indicated some psychiatric complaints as defined by scores above 60 in the respective categories. Yet, the average of these scores does not indicate overt psychiatric symptoms in the patient population included in this study (see Table 2).…”
Section: Discussionmentioning
confidence: 97%
“…depression or anxiety, an autonomic dysbalance with decreased parasympathetic modulation has been described. For instance, both short and long-term complexity measures of heart rate modulation indicating parasympathetic activity have been shown to be reduced in major depression [15,16] or during treatment [17]. Furthermore, a relative decrease of vagal activity has repeatedly been described for anxiety [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…17 Others are regarded to be more specific, for instance smooth pursuit eye movement dysfunction, which is known to reflect a genetic vulnerability to schizophrenia (eg, ocular motor abnormalities). 15 Autonomic dysfunction associated with decreased vagal and increased sympathetic modulation occurs in various psychiatric conditions such as major depression, 18 anxiety disorders 19,20 or alcohol dependency, and withdrawal. 21,22 Thus, one could assume that autonomic dysfunction is rather less likely to be specific for one disease.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this study was thus to investigate the possible link between HRV complexity and sympathetic outflow to the heart. We evaluated cardiac norepinephrine (NE) spillover (the gold standard of measuring cardiac sympathetic outflow) and HRV in healthy subjects and patients with a diagnosis of major depression or panic disorder, conditions known to be associated with an altered cardiac autonomic function (4). These patients encompass a wide range of sympathetic outflow levels, from normal to abnormal, while their cardiac substrate remains preserved.…”
mentioning
confidence: 99%